How Related are Interbank and Lending Interest Rates? Evidence on Selected European Union Countries - Tomáš Heryán; Daniel Stavárek (European Financial and Accounting Journal, 2010)
This paper investigates the nature of the causal relationships among interbank market interest rates and corporate loans interest rates in four countries from the euro area (Austria, Belgium, France and Italy), and in the Czech Republic. The paper also estimates a development of bank credit margin in banking industries of these countries in period from January 2004 to March 2010. Using Johansen cointegration and Granger causality tests on monthly data we investigate long-term as well as short-term causalities between the interest rates. The results suggest that interest rate relationships differ in all selected countries, and also that foreign majority owners of the Czech banks could affect interest rate policy of the subsidiaries to offset losses realized by the parent banks.
Keywords: C32; E40; E43; E52; F36; 650; Cointegration; Granger Causality; Interbank Interest Rates; Lending Interest Rates; European Union